Implementation of Deep Back Massage to Reduce Pain Intensity in Maternity - Wulandari, Amri; Rustianingsih, Lina; Putrianti, Berlina (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The maternal mortality and illness rate in Indonesia is still high. In 2022, the number of maternal deaths in Indonesia was 3,572 cases (Kemenkes RI, 2023). The number of maternal deaths in Sleman Regency in 2022 is 11 cases with a maternal mortality rate of 91.61 per 100,000 live births. The cause of maternal death in Sleman Regency was due to bleeding (4), preeclampsia (2), acute respiratory distress syndrome (ADRS) severe degrees due to lung problems (1), septic shock (1), sepsis (1), heart disease (1), and ileus (1). Based on the results of the perinatal maternal audit in Sleman Regency of the 11 deaths, 7 deaths did not experience delays and 4 experienced delays in making decisions to refer, both from family decisions and decisions from health workers who handle patients (Sleman Health Office, 2023). So midwifery care Continuity Of Care It needs to be implemented as an effort to reduce maternal mortality rates. Purpose: To find out the results of the implementation deep back massage to reduce the intensity of pain in pregnant women during the first active phase. Method: This type of research is qualitative research with a case study method and uses an approach Continuity of Care Mrs. R was 23 years old. Result: After doing deep back massage During Phase I Active Phase labor, the mother's pain decreases from a pain scale of 8 to 6. Conclusion: It can be concluded that the implementation of deep back massage in pregnant women during the first active phase, it can reduce pain.